Symptom severity and health-related quality of life in patients with atrial fibrillation: findings from the observational ARENA study - Sadlonova, Monika; Senges, Jochen; Nagel, Jonas; Celano, Christopher; Klasen-Max, Caroline; Borggrefe, Martin; Akın, Ibrahim; Thomas, Dierk; Schwarzbach, Christopher Jan; Kleemann, Thomas; Schneider, Steffen; Hochadel, Matthias; et al. (Journal of Clinical Medicine, 2022)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is associated with impaired health-related quality of life (HRQoL), high symptom severity, and poor cardiovascular outcomes. Both clinical and psychological factors may contribute to symptom severity and HRQoL in AF. Methods: Using data from the observational Atrial Fibrillation Rhine-Neckar Region (ARENA) trial, we identified medical and psychosocial factors associated with AF-related symptom severity using European Heart Rhythm Association symptom classification and HRQoL using 5-level EuroQoL- 5D. Results: In 1218 AF patients (mean age 71.1 ± 10.5 years, 34.5% female), female sex (OR 3.7, p < 0.001), preexisting coronary artery disease (CAD) (OR 1.7, p = 0.020), a history of cardioversion (OR 1.4, p = 0.041), cardiac anxiety (OR 1.2; p < 0.001), stress from noise (OR 1.4, p = 0.005), work-related stress (OR 1.3, p = 0.026), and sleep disturbance (OR 1.2, p = 0.016) were associated with higher AF-related symptom severity. CAD (β = −0.23, p = 0.001), diabetes mellitus (β = −0.25, p < 0.001), generalized anxiety (β = −0.30, p < 0.001), cardiac anxiety (β = −0.16, p < 0.001), financial stress (β = −0.11, p < 0.001), and sleep disturbance (β = 0.11, p < 0.001) were associated with impaired HRQoL. Conclusions: Psychological characteristics, preexisting CAD, and diabetes may play an important role in the identification of individuals at highest risk for impaired HRQoL and high symptom severity in patients with AF.